Vindogentianine, a hypoglycemic alkaloid from Catharanthus roseus (L.) G. Don (Apocynaceae) - Tiong, S.H.; Looi, C.Y.; Arya, Aditya; Wong, Won Fen; Hazni, Hazrina; Mustafa, Mohd Rais; Awang, Khalijah (Elsevier, 2015)
Vindogentianine, a new indole alkaloid together with six known alkaloids, vindoline, vindolidine, vindolicine, vindolinine, perivine and serpentine were isolated from leaf extract (DA) of Catharanthus roseus (L.) G. Don. Their structures were elucidated by spectroscopic methods; NMR, MS, UV and IR. Vindogentianine is a dimer containing a vindoline moiety coupled to a gentianine moiety. After 24 h incubation, vindogentianine exhibited no cytotoxic effect in C2C12 mouse myoblast and β-TC6 mouse pancreatic cells (IC50 > 50 μg/mL). Real-time cell proliferation monitoring also indicated vindogentianine had little or no effect on C2C12 mouse myoblast cell growth at the highest dose tested (200 μg/mL), without inducing cell death. Vindogentianine exhibited potential hypoglycemic activity in β-TC6 and C2C12 cells by inducing higher glucose uptake and significant in vitro PTP-1B inhibition. However, in vitro α-amylase and α-glucosidase inhibition assay showed low inhibition under treatment of vindogentianine. This suggests that hypoglycemic activity of vindogentianine may be due to the enhancement of glucose uptake and PTP-1B inhibition, implying its therapeutic potential against type 2 diabetes.